Product-Form Stationary Distributions for Deficiency Zero Networks with Non-mass Action Kinetics - Anderson, David F.; Cotter, Simon L. (Bulletin of mathematical biology, 2016)
In many applications, for example when computing statistics of fast subsystems in a multiscale setting, we wish to find the stationary distributions of systems of continuous-time Markov chains. Here we present a class of models that appears naturally in certain averaging approaches whose stationary distributions can be computed explicitly. In particular, we study continuous-time Markov chain models for biochemical interaction systems with non-mass action kinetics whose network satisfies a certain constraint. Analogous with previous related results, the distributions can be written in product form.